Critical Synthesis Package: Utrecht Work Engagement Scale (UWES) - Jane Rosenthal (Association of American Medical Colleges, 2014)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to heath science education of the Utrecht Work Engagement Scale (UWES), and (2) a copy of the UWES Instrument and the preliminary scoring manual developed by Wilmar B. Schaufeli, PhD. The UWES is a self-administered instrument with nine items divided into three subscales of Vigor (levels of energy, resilience, not easily fatigued, persistence, willingness to invest effort), Dedication (finding significance, enthusiasm, pride in one's work, feeling inspired and challenged by one's work), and Absorption (totally and happily immersed in one's work, and having difficulties leaving one's work because of time passing quickly and forgetting other things). Longer versions of the instrument are also available (UWES-17, UWES-15), and there is a student version that utilize the same subscales. Items are scored along a 6-point Likert-type scale (0 = Never to 6 = Always or Every day). Scores are totaled to give an overall picture of engagement in work with the higher score indicating higher engagement. Higher scores of engagement have been shown to be the antithesis of burnout and have been shown to be predictive of job performance and client satisfaction. However, more studies need to be conducted in the area of health care as it is unclear whether engagement can be predictive of increased productivity, longevity, and patient outcomes.